P80 Antibiotic usage as a risk factor for non-tuberculous mycobacterium infection in children with cystic fibrosis. (14th November 2013) - Bowker, JL; Thomas, MF; O'Brien, CJ
Abstract : Background: There is a growing incidence of Non-Tuberculous Mycobacterium (NTM) in children with Cystic Fibrosis. This audit aimed to determine relevant risk factors for NTM acquisition in paediatric cystic fibrosis patients. Methods: Data was obtained from clinical notes for 66 patients aged 5–18 years old in a North-East CF clinic who had sputum or bronchoalveolar lavage screened for NTM between 2011 and 2012. Results: Patients who isolated NTM had higher exposure to intravenous antibiotic courses than comparison group: 53 vs. 21% having 3 or more courses per year (p-value 0.039). 77% of NTM positive patients vs. 47% of non-NTM were taking long-term azithromycin (p-value 0.07). Conclusion: Higher exposure to intravenous antibiotics courses is a risk factor for isolation of NTM in CF children. This highlights the importance of close monitoring until more is known about the long term health implications of this group of pathogens.